2015
DOI: 10.1590/0103-6440201300234
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Surface Treatments for Ceramic Bracket Base on Bond Strength of Rebonded Brackets

Abstract: The aim of this study was to evaluate the shear bond strength of rebonded ceramic brackets after subjecting the bracket base to different treatments. Seventy-five premolars were selected and randomly distributed into five groups (n=15), according to the type of the bracket surface treatment: I, no treatment, first bonding (control); II, sandblasting with aluminum oxide; III, sandblasting + silane; IV, silica coating + silane; and V, silicatization performed in a laboratory (Rocatec system). The brackets were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The results of this study were in accordance with previous research which stated that the sandblasting procedure was effective to clean the surface of the bracket base and increase the strength of ceramic bracket attachment. 10 The area around the microporosity was a white particle of various sizes which is zirconia attached to the base of the bracket base and can be an instrument to enhance attachment. Zirconia particles have a large adsorption capacity against phosphate groups silane, the phosphoric methacrylate.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study were in accordance with previous research which stated that the sandblasting procedure was effective to clean the surface of the bracket base and increase the strength of ceramic bracket attachment. 10 The area around the microporosity was a white particle of various sizes which is zirconia attached to the base of the bracket base and can be an instrument to enhance attachment. Zirconia particles have a large adsorption capacity against phosphate groups silane, the phosphoric methacrylate.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22] Sandblasting the debonded ceramic bracket bases before rebonding has been studied as a surface-treatment technique and resulted in a lower SBS than new brackets. 14 Application of silane after sandblasting for improving the SBS was studied by many authors, controversy found in literature as silane was reported to decrease SBS 23 , also reported to increase in the SBS 24,25 and reported that it had no effect on SBS 14…”
Section: Volume 47 -June 2015mentioning
confidence: 99%
“…Adhesive remnants of the dislodged brackets had been conventionally removed in-office by using green stones [ 12 ], direct flame [ 13 ], tungsten-carbide bur [ 14 ], sandblasting [ 15 ], silica coating [ 16 ], or laser application [ 17 ]. Even though these methods can be easily performed out in the dental office with minimal cost, there is no consensus as to which is the best method to remove adhesive remnants from the bracket base.…”
Section: Introductionmentioning
confidence: 99%